PERAN SANTRI DALAM MEWUJUDKAN INDONESIA EMAS 2045 - Kurdi, Moh. (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2022)
Indonesia Gold is the ideal of the nation where in order to realize this, various strategic, tactical and innovative steps must be taken. Therefore, it is necessary to have an early development regarding the prospects for education and economic development. Pesantren is the oldest Islamic educational institution in Indonesia which has great potential to realize development in both aspects through the development of human resources from an early age. So that with this, a productive, innovative and progressive golden generation of the nation can be created as an asset or human capital to manage the nation towards a Golden Indonesia 2045. The method used in this research is a conceptual qualitative method to provide a detailed explanation of the role of santri. The article explains how the role of santri for the nation, the role of santri in education and the role of santri in the economy.